PP.39.13: RELATION BETWEEN FEMORAL BONE MINERAL DENSITY AND AORTIC CALCIFICATIONS IN RENAL TRANSPLANTED PATIENTS. (June 2015) - Alfieri, C.; Regalia, A.; Meneghini, M.; Gandolfo, M.T.; Binda, V.; Cresseri, D.; Campise, M.R.; Croci, M.D.; Messa, P.
Abstract : Objective: Bone and cardiovascular disorders(CD) are relevant problems during kidney transplantation(KTx), especially during the 1styear. High interest in bone mineral density(BMD) in relation with vascular calcifications(VC)andCD is nowadays present. Our study wants to evaluate, in KTx pts:1)the prevalence of femoral osteopenia(OP)and osteoporosis(OS);2)the factors related to femoral BMD(F-BMD);3)the relationship between F-BMD and aortic calcifications(ACI);4)the role of F-BMD in predicting CD during the 1styear of KTx. Design and method: 293-KTx pts transplanted between2004 and 2013 were evaluated. Clinical parameters, fasting blood and urinary samples were collected at 1st(T0) and 12thmth(T12) after KTx. In addition, at the same time:1)in 170 FGF-23, Fetuin and 25OH-VitD were dosed;2)F-BMD(g/cm2), assessed by DEXA, was performed. T-score -1 > T>-2.5 was considered OP whereas T-score < -2.5 OS; 3)in 115 pts a Lumbar X-Ray for the ACI evaluation(Kauppila score)was performed. ACI progression(ACI-Prog) was determined by their simple increase. CD was defined by a major disease affecting heart (f.i. stroke, arrhythmia) or vascular (f.i. stenosis/thrombosis) system. Results: At T0 and T12 OP was present in 53%and52%of patients, OS in 15%and12%. At T0, F-BMD correlated directly with BMI, alkaline-phosphatase (ALP), fetuin, FGF-23 and 25OH-VitD (p = 0.003;p = 0.01;p = 0.02;p = 0.005)and inversely with the age, time of dialysis and s-P(p < 0.0001;p = 0.01;p = 0.03). At T12, a direct correlation with BMI, FGF-23 and fetuin (p = 0.001;p = 0.04, p = 0.003) and an inverse one with age and time of dialysis (p < 0.0001;p = 0.001) were found. In multivariate analysis age and fetuin resulted able in determining F-BMD, at T0 in addition to ALP and P. At T0 and T12, ACI were present in 55%and in61% of pts. Both at T0andT12 ACI were more in pts with abnormal F-BMD(p = 0.06–p = 0.01), without differences between OP and OS. During follow-up, in 26%of ptsACI-Prog was found. Their F-BMD was lower both at T0 and T12(p = 0.01;p = 0.03). Using ROC-curve, F-BMD showed a predictive role of ACI-Prog (T0:AUC0.65–p = 0.02;T12:AUC0.69-p = 0.005). During follow-up, 8pts had a CD. Their T0-T12 F-BMD were not different with those of CD-free pts. Conclusions: 1) The prevalence of OPandOS is quite high in KTx. Fetuin and age influence independently F-BMD. 2) ACI are present approximately in half of patients. A small degree ofACI-progr was found. F-BMD could be a indirect indicator of ACI and of ACI-progr. 3)F-BMD seems not able to predict CV during the 1styear of KTx. Our results confirm a cross-link between bone mineralization and VC in KTx patients.